Co-parasitism of intestinal protozoa and Schistosoma japonicum in a rural community in the Philippines - Kosala Gayan Weerakoon; Catherine A. Gordon; Gail M. Williams; Pengfei Cai; Geoffrey N. Gobert; Remigio M. Olveda; Allen G. Ross; David U. Olveda; Donald P. McManus (BMC, 2018)
Abstract Background Co-parasitism is a frequent occurrence in impoverished communities in the tropics resulting in a considerable disease burden. While there are extensive reports of intestinal helminthiases, including schistosomiasis japonica, the occurrence and extent of diseases caused by intestinal protozoa (IP) have yet to be investigated in depth in the Philippines. We present a detailed analysis of polyparasitism in a rural community of Northern Samar, focusing on co-infections of IP with Schistosoma japonicum. Methods A descriptive cross sectional study was carried out in 2015 across 18 barangays (villages) endemic for S. japonicum in Northern Samar, the Philippines to assess the burden of human schistosomiasis and IP infections. Faecal samples collected from 412 participants from the 18 barangays were included in the final molecular analysis. A multiplex quantitative PCR assay was developed and used for the detection of Blastocystis spp., Entamoeba histolytica, Cryptosporidium spp. and Giardia duodenalis in stool samples. The findings were combined with previous results of droplet digital PCR diagnosis of individuals from the same 18 barangays infected with S. japonicum determined using the same stool samples for analysis. Results Mean age of the study participants was 40.3 years (95% CI: 38.8-41.8) with 53% (n = 218) being males. Prevalence of S. japonicum (74.5%) and Blastocystis spp. (58.7%) was significantly higher compared to other infections, with E. histolytica having the lowest prevalence (12.1%). A majority of individuals were infected with more than one parasite with two infections being most common (n = 175, 42.5%). The prevalence of individuals with two parasites was significantly higher than all others with 27.9% (n = 115) subjects harbouring a single parasite species. Of individuals with two infections, S. japonicum and Blastocystis spp. were the most common combination (n = 110, 62.9%). Examining age within the population, 58.5% (n = 38) of school-aged children and 60.1% (n = 14) of women of child bearing age harboured at least two parasite species. Conclusions The study revealed that polyparasitism with IP infections and schistosomiasis japonica is highly prevalent in individuals in Northern Samar which likely contributes to the significant public health and socio-economic burden suffered by this population. More generally, the findings are of relevance when considering implementation of integrated control strategies for intestinal parasites.